Electoral change through generational replacement: An age-period-cohort analysis of vote choice across 21 countries between 1948 and 2021 - Rekker, Roderik (Frontiers in Political Science, 2024)
People’s generation may have become one of the core predictors of their vote choice. This study examines this hypothesis across 21 Western established democracies between 1948 and 2021. An age-period-cohort analysis on 258 national election surveys (N = 462.084) reveals that the most recent generations are much less likely to vote for the major right-wing party in two-party systems. In multi-party systems, the gradual decline of Christian democratic parties has been largely driven by the generational replacement of pre-WW2 cohorts. Social democratic and conservative parties may face a challenge in future decades because their support is particularly low among the most recent generations whereas liberal, socialist, and particularly green parties stand to gain from generational replacement. Far-right parties have been least popular among voters who came of age during the 1930s and 1940s. A small life-cycle effect points out that people over the age of 65 vote slightly more conservative.